Uncovering EFL learners' demotivation towards English online learning during the Covid-19 pandemic in Indonesia - Erna Iftanti; Imelda Imelda; Wisma Yunita (Universitas Syiah Kuala, 2023)
Online learning during the Covid-19 pandemic has demotivated Indonesian tertiary EFL students to learn English, which affected their English performance and achievement. This article ferrets out the features of the EFL students' demotivation, the factors affecting their demotivation, the solution to reduce their demotivation, and the implication of their demotivation towards their English performances and achievement. The data for this descriptive quantitative research were collected through an online open-ended questionnaire to the EFL students of two Islamic state colleges in East Java, Indonesia. The questionnaire was distributed when the Covid-19 pandemic was still at its peak. There were 71 out of 76 respondents who completed the questionnaire claimed to experience demotivation with online learning mode. The data from those 71 respondents were then analyzed descriptively. The results of this study indicate that online learning experiences were found to be the main factor that affected their demotivation. This was further evident in their English performance and achievement. Meanwhile, the aspects of teachers, online learning infrastructures, family, and student-related demotivators contributed to conducting effective online learning. This study utilized qualitative data from the learners' perspective so that further studies which take a different perspective, such as family, teachers, lecturers, and policymakers, would enrich these findings.